(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This article is a contribution to the implementation of a real-time energy management system (EMS) to maximize the efficiency of power distribution in an isolated hybrid system containing photovoltaic modules, a wind turbine and a battery energy storage system which is used as a backup source. However, hybridization of multiple sources requires power flow control. For this reason, in this work, an appropriate power management is developed using a fuzzy deterministic rule-based algorithm to control the proposed autonomous multi-source system. The developed EMS is tested and validated by an application of arc welding in isolated industrial sites located in a remote region of the Algerian Sahara.